Pengaruh Brand Image dan Kualitas Produk Terhadap Keputusan Pembelian Produk Lip Tint - Dzilla Khoerunnisa; Halimah Zahrah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The growth of the cosmetic industry in Indonesia has intensified brand competition, particularly in lip tint products that are increasingly popular among university students. This study aims to analyze the influence of brand image and product quality on purchasing decisions of Barenbliss lip tint among Management Study Program students of the Muhammadiyah University of Bandung. This research employs a quantitative method with a survey approach. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with statistical software. The results indicate that brand image has a positive and significant effect on purchasing decisions. Product quality also shows a positive and significant influence on purchasing decisions and is found to be more dominant than brand image. Simultaneously, brand image and product quality significantly affect purchasing decisions for Barenbliss lip tint. These findings suggest that students’ purchasing decisions are strongly influenced by their perceptions of product quality and brand image. Therefore, companies are encouraged to continuously improve product quality and strengthen brand image to enhance consumer purchasing decisions, particularly among students.